Assembling Japan Modernity, Technology and Global Culture - Kirsch, Griseldis; Martinez, Dolores P.; White, Merry (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2015)
Assembling Japan focuses on Japan's modernization as a long-term process that is reliant on changing technology and that has led to the nation's full engagement with the global system. This process forms a complex field of tensions, full of interesting dynamisms and synergies that can be best understood through the book's methodology: anthropological analysis combined with historical contextualization. The approaches in this collection are manifold. Some chapters examine the themes of modernity, technology and Japan's global experience though popular culture, from reggae to football, from television to film. Other topics include coffee, travel, economics, cultural politics and technological innovation in the field of robotics. All of the contributions aim to show how these global interactions have occurred and continue to take place in twenty-first-century Japan.
Keywords: japonská architektura; technologie; globální společnost; Japanese architecture; technology; global society; Japonsko; Japan; elektronické knihy; electronic books